Hetero-Diels–Alder reactions of hetaryl and aryl thioketones with acetylenic dienophiles - Mlostoń, Grzegorz; Grzelak, Paulina; Mikina, Maciej; Linden, Anthony; Heimgartner, Heinz (Beilstein Journal of Organic Chemistry, 2015)
Selected hetaryl and aryl thioketones react with acetylenecarboxylates under thermal conditions in the presence of LiClO4 or, alternatively, under high-pressure conditions (5 kbar) at room temperature yielding thiopyran derivatives. The hetero-Diels–Alder reaction occurs in a chemo- and regioselective manner. The initially formed [4 + 2] cycloadducts rearrange via a 1,3-hydrogen shift sequence to give the final products. The latter were smoothly oxidized by treatment with mCPBA to the corresponding sulfones.
Keywords: dimethyl acetylenedicarboxylate (DMAD); hetero-Diels–Alder reactions; high pressure reactions; methyl propiolate; thioketones; thiopyrans

Targets in Heterocyclic Systems; Chemistry and Properties - Mlostoń, G.; Heimgartner, H. (Italian Society of Chemistry, 2005)

Targets in Heterocyclic Systems; Chemistry and Properties - Mlostoń, G.; Heimgartner, H. (Italian Society of Chemistry, 2006)

(untitled) - Okuma, K. (Sulfur Rep., 2002)

(untitled) - Huisgen, R.; Fisera, L.; Giera, H.; Sustmann, R. (J. Am. Chem. Soc., 1995)

(untitled) - Huisgen, R.; Langhals, E. (Heteroat. Chem., 2006)

(untitled) - Huisgen, R.; Li, X.; Giera, H.; Langhals, E. (Helv. Chim. Acta, 2001)

(untitled) - Schatz, J.; Sauer, J. (Tetrahedron Lett., 1994)

(untitled) - Rohr, U.; Schatz, J.; Sauer, J. (Eur. J. Org. Chem., 1998)

(untitled) - Gotthardt, H.; Nieberl, S. (Liebigs Ann. Chem., 1980)

(untitled) - Rapp, J.; Huisgen, R. (Tetrahedron, 1997)

(untitled) - Huisgen, R.; Rapp, J. (Heterocycles, 1997)

(untitled) - Ohno, A.; Koizumi, T.; Ohnishi, Y. (Bull. Chem. Soc. Jpn., 1971)

(untitled) - Okuma, K.; Yamamoto, T.; Shirokawa, T.; Kitamura, T.; Fujiwara, Y. (Tetrahedron Lett., 1996)

(untitled) - Ohmura, H.; Motoki, S. (Bull. Chem. Soc. Jpn., 1984)

(untitled) - Saito, T.; Shizuta, T.; Kikuchi, H.; Nakagawa, J.; Hirotsu, K.; Ohmura, H.; Motoki, S. (Synthesis, 1994)

(untitled) - Mlostoń, G.; Urbaniak, K.; Gębicki, K.; Grzelak, P.; Heimgartner, H. (Heteroat. Chem., 2014)

The Diels-Alder Reaction; Selected Practical Methods - Fringuelli, F.; Taticchi, A. (J. Wiley & Sons Ltd., 2002)

(untitled) - Matsumoto, M.; Hamana, H.; Iida, H. (Helv. Chim. Acta, 2005)

ORTEP II, Report ORNL-5138 - Johnson, C. K. (Oak Ridge National Laboratory, 1976)

(untitled) - Aitken, R. A.; Hauduc, C.; Hossain, M. S.; McHale, E.; Schwan, A. L.; Slawin, A. M. Z.; Stewart, C. A. (Aust. J. Chem., 2014)

(untitled) - Okuma, K.; Kojima, K.; Koga, Y.; Shioji, K. (Heterocycles, 2000)

(untitled) - Kaminskyy, D.; Kryshchyshyn, A.; Nektegayev, I.; Vasylenko, O.; Grellier, P.; Lesyk, R. (Eur. J. Med. Chem., 2014)

(untitled) - Tavakolinia, F.; Baghipour, T.; Hossaini, Z.; Zareyee, D.; Khalilzadeh, M. A.; Rajabi, M. (Nucleic Acid Ther., 2012)

(untitled) - Rajabi, M.; Khalilzadeh, M. A.; Mehrzad, J. (DNA Cell Biol., 2012)

(untitled) - Daraosheh, A. Q.; Görls, H.; El-khateeb, M.; Mlostoń, G.; Weigand, W. (Eur. J. Inorg. Chem., 2011)

(untitled) - Daraosheh, A. Q.; Apfel, U.-P.; Görls, H.; Friebe, C.; Schubert, U.-S.; El-khateeb, M.; Mlostoń, G.; Weigand, W. (Eur. J. Inorg. Chem., 2012)